Teacher stories - Inspiring good practices - a booklet of educator stories - Pöntynen Riitta; Nyroos Sari (InCompEdu project, 2025)
“Teacher stories” - Inspiring good practices - a booklet of educator stories is based on the results of an extensive survey in the partner countries of InCompEdu project (Erasmus+): Croatia, Finland, Italy, Poland, Romania and Slovenia. First, experiences, challenges and best practices related to online teaching were collected from academic teachers with a questionnaire. In the second phase, in total 57 interviews were done by the project partners. This booklet, “Teacher stories” presents the results, with quotes and stories of the teachers who took part in the survey. The results are grouped according to the themes which
emerged from the questionnaire and the interviews.